A classroom example of the deleterious effects of auditor predictability. Issue 1 (March 2015) - Spires, Eric E.; Ward, C.J.
Highlights Students play the role of a fraudster and insert misstatements in an account. The instructor "audits" the account in both a predictable and unpredictable way. Predictability is shown to increase the chances of fraud going undetected. Formal statistical analyses support and generalize the exercise-based findings. Real fraud cases involving auditor predictability are discussed.